2017
DOI: 10.1007/s10886-017-0910-4
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Sexual Pheromones Questions their Role in Bumblebee Pre-Mating Recognition System

Abstract: Sex-specific chemical secretions have been widely used as diagnostic characters in chemotaxonomy. The taxonomically confused group of bumblebees has reaped the benefit of this approach through the analyses of cephalic labial gland secretions (CLGS). Most of currently available CLGS descriptions concern species from the West-Palearctic region but few from the New World. Here, the CLGS of four East-Palearctic species Bombus deuteronymus, B. filchnerae, B. humilis, and B. exil (subgenus Thoracobombus) are analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…As mentioned in Brasero et al 2017 about B. muscorum and B. filchnerae , the CLGS composition of B. pensylvanicus also includes very low concentrations of compounds below 18 carbons. This observation therefore strengthens our hypothesis, suggesting that the long pre-mating recognition distance could be mediated by cues other than the CLGS such nest site choice (i.e., the habitat) or nest scent (Brasero et al 2017).…”
Section: B Pensylvanicus Groupsupporting
confidence: 86%
See 3 more Smart Citations
“…As mentioned in Brasero et al 2017 about B. muscorum and B. filchnerae , the CLGS composition of B. pensylvanicus also includes very low concentrations of compounds below 18 carbons. This observation therefore strengthens our hypothesis, suggesting that the long pre-mating recognition distance could be mediated by cues other than the CLGS such nest site choice (i.e., the habitat) or nest scent (Brasero et al 2017).…”
Section: B Pensylvanicus Groupsupporting
confidence: 86%
“…However, even if this population is very similar to the population of Chiapas, major differentiations are found in abundant and minor compounds (Figure 2, Supplementary file 2). Such cases have already been described by comparing different species such as B. filchnerae and B. muscorum (Brasero et al 2017), as well as within the Cullumanobombus subgenus .…”
Section: B Pensylvanicus Groupmentioning
confidence: 82%
See 2 more Smart Citations
“…For these taxa, we observed quantitative differences involving very minor compounds (median < 0.20%) close to our threshold of 0.1% which have probably not a major role in pre-mating recognition (Appendix S2). Brasero et al (2017) and Terzo et al (2005) showed intraspecific variability in the CLGS of different bumblebee species. Several compounds could be abundant or absent according to the specimen analyzed.…”
Section: Differentiation Of Helleri/alpinus Hyperboreus/natvigi Amentioning
confidence: 98%